Validity of E-LAPD Based on The Learning Cycle 7-E Model to Improve Critical Thinking Skills Oriented to Multiple Chemical Representations in Reaction Rate Factors Submaterial - Sari, Rahmania Fitrah; Salsa Sabrina Fajar Maulidiah; Liza Nurrahma Dwi Agustin; Novita, Dian (Universitas Negeri Surabaya, 2025)
This research aims to describe the validity of the Electronic Learner Activity Sheet (E-LAPD) for reaction rate to improve critical thinking skills with the 7-E learning cycle learning model developed. The development model in this research is ADDIE with four stages Analyze, Design, Development, and Evaluate. The validation results were analyzed based on the mode in each aspect. Based on the validation results, it was found that the developed reaction rate E-LAPD has a good category with a score of 3 on the content validity aspect and a good category with a score of 3 on construct validity. Furthermore, reaction rate electronic learner activity sheet can be used in the learning process in the classroom to determine the practically and effectiveness of the developed reaction rate electronic worksheet